Perkembangan, metode pendekatan dan tantangan manajemen sumber daya manusia - Ni Wayan Mujiati (Forum Manajemen, 2023)
The development of human resource management (HR) is driven by the progress of civilization, scientific education and the demands of society to compete, survive and develop in producing goods or services. Experts in the 20th century developed HRM into a field of study that specifically studies the role of human development in achieving organizational or company goals. The three approaches used to understand human resource management are: a) conventional or mechanical approaches; b) paternalistic approach; c) social or contemporary systems approach. Human resource management challenges are relatively tougher to face in countries where corporate culture is more dependent on top managers or company owners. Identified challenges faced by HRM that need to be overcome in the face of an open business, full of competition in a free trade system including: external challenges and internal or organizational challenges.